2019
DOI: 10.1111/ijac.13389
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐oriented low‐cost Al2O3 ceramics with hierarchical pore structure fabricated from SiC solid waste

Abstract: Environment‐oriented low‐cost Al2O3 reticulated porous ceramics with hierarchical pore structure were fabricated by the polymer sponge replica method combined with vacuum infiltration methods, using Al2O3 powders and SiC solid waste (SCSW) as raw material and a pore‐forming agent. The effects of SCSW addition amount on mechanical properties, microstructure and pore size of Ceramics were investigated. The results showed that the thermal shock resistance of specimens increased gradually with addition of SCSW, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[6][7][8][9] On the other hand, the waste primarily consists of oxides, which are comparable to the components of refractories; hence, using waste in refractories is a viable alternative. [10][11][12][13] Furthermore, due to the high-cost of raw materials, there is a trend to use low-cost industrial waste in refractories by partially replacing expensive commercial raw material for blast furnaces, kilns, and incinerators, particularly during the current recession. 14,15 Kumar et al 16,17 used ferro-chromium slag as aggregate to prepare a castable refractory with great compressive strength values using.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] On the other hand, the waste primarily consists of oxides, which are comparable to the components of refractories; hence, using waste in refractories is a viable alternative. [10][11][12][13] Furthermore, due to the high-cost of raw materials, there is a trend to use low-cost industrial waste in refractories by partially replacing expensive commercial raw material for blast furnaces, kilns, and incinerators, particularly during the current recession. 14,15 Kumar et al 16,17 used ferro-chromium slag as aggregate to prepare a castable refractory with great compressive strength values using.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous literatures on industrial waste utilization in partial substitution of concrete for construction have been reported for replacement applications 6–9 . On the other hand, the waste primarily consists of oxides, which are comparable to the components of refractories; hence, using waste in refractories is a viable alternative 10–13 . Furthermore, due to the high‐cost of raw materials, there is a trend to use low‐cost industrial waste in refractories by partially replacing expensive commercial raw material for blast furnaces, kilns, and incinerators, particularly during the current recession 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several methods had been used to resolve the inherent brittleness issues, including (1) incorporation of reinforcement material (fibres or granular powder) within the ceramic matrix [1], (2) hierarchical porous ceramics structures [2,3], (3) laminated composite materials, [4] (4) phase transformation toughening induced by applied stress [5], (5) nanocrystalline ceramics material [6], and (6) microcrack toughening [7]. For this paper, we will be focusing on the incorporation of reinforcement material and hierarchical structure within the ceramic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the safe utilization of tailings and metallurgical slags as alternative raw materials of CPCs are of great concerns [11]. Up to now, many researchers have found that CPCs with better performance could be obtained by applying different industrial solid wastes as raw materials and supplementing appropriate additive components to adjust the contents of variant chemicals ) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%